2021
DOI: 10.3390/ijms22084231
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biophysical Characterization of Recombinant Human 3-Phosphoglycerate Dehydrogenase

Abstract: The human enzyme D-3-phosphoglycerate dehydrogenase (hPHGDH) catalyzes the reversible dehydrogenation of 3-phosphoglycerate (3PG) into 3-phosphohydroxypyruvate (PHP) using the NAD+/NADH redox cofactor, the first step in the phosphorylated pathway producing L-serine. We focused on the full-length enzyme that was produced in fairly large amounts in E. coli cells; the effect of pH, temperature and ligands on hPHGDH activity was studied. The forward reaction was investigated on 3PG and alternative carboxylic acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…The K m,3‐PHP and K m,OPS are significantly higher than the in vivo substrate concentration (Table 1), suggesting that PSAT works under k cat / K m regime in the cell and is thus a sensor for the levels of 3‐PHP, regulating its activity based on the availability of the glycolysis‐derived substrate. OPS formation by PSAT is 300‐fold more efficient than the reverse reaction and, considering a K eq of about 10, the equilibrium of the whole pathway is shifted towards product formation, counteracting the unfavorable equilibrium of the first reaction catalyzed by PHGDH in the PP (Murtas et al, 2020; Murtas et al, 2021). Notably, human PSAT activity is strongly stimulated by increasing the ionic strength, that is, by 200 mM KCl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The K m,3‐PHP and K m,OPS are significantly higher than the in vivo substrate concentration (Table 1), suggesting that PSAT works under k cat / K m regime in the cell and is thus a sensor for the levels of 3‐PHP, regulating its activity based on the availability of the glycolysis‐derived substrate. OPS formation by PSAT is 300‐fold more efficient than the reverse reaction and, considering a K eq of about 10, the equilibrium of the whole pathway is shifted towards product formation, counteracting the unfavorable equilibrium of the first reaction catalyzed by PHGDH in the PP (Murtas et al, 2020; Murtas et al, 2021). Notably, human PSAT activity is strongly stimulated by increasing the ionic strength, that is, by 200 mM KCl.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammalian central nervous system (CNS), the PP is crucial for maintaining the levels of L‐Ser, as this nonessential amino acid is transported inefficiently through the blood–brain barrier. The first step of the PP is catalyzed by 3‐PG dehydrogenase (PHGDH; Murtas et al, 2021; Unterlass et al, 2017) which oxidizes 3‐PG to 3‐phosphohydroxypyruvate (3‐PHP) using NAD + as the electron acceptor. The equilibrium of this reaction is strongly shifted in favor of 3‐PG (Grant, 2012; Murtas et al, 2020); therefore, the subsequent reactions of the pathway must provide a thermodynamic drive to synthesize L‐Ser.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that extracellular levels of L-and D-Ser were reduced at an early stage of AD, before b-amyloid plaque was deposited in the hippocampus of a mouse model that displays lower glycolytic flux in hippocampal astrocytes (Le Douce et al, 2020). The glycolytic flux may control brain L-Ser synthesis (Figure S5); phosphoglycerate kinase (PGK) and phosphoglycerate mutase (PGM1) are mainly responsible for the relatively high levels of cellular L-Ser (0.18-0.55 mM) (Jin et al, 2020) because the K M of human PHGDH for 3PG (0.36 mM) is larger than its cellular level (Murtas et al, 2021). Although human PHGDH activity is not affected by L-Ser (Murtas et al, 2021), the pyruvate kinase M2 isoform (PKM2, mainly expressed in tumor cells and in astrocytes) is activated by L-Ser binding (Chaneton et al, 2012), supporting glycolysis and lactate production.…”
Section: Discussionmentioning
confidence: 99%
“…The glycolytic flux may control brain L-Ser synthesis (Figure S5); phosphoglycerate kinase (PGK) and phosphoglycerate mutase (PGM1) are mainly responsible for the relatively high levels of cellular L-Ser (0.18-0.55 mM) (Jin et al, 2020) because the K M of human PHGDH for 3PG (0.36 mM) is larger than its cellular level (Murtas et al, 2021). Although human PHGDH activity is not affected by L-Ser (Murtas et al, 2021), the pyruvate kinase M2 isoform (PKM2, mainly expressed in tumor cells and in astrocytes) is activated by L-Ser binding (Chaneton et al, 2012), supporting glycolysis and lactate production. Conversely, at low L-Ser levels, the glycolytic flux to lactate is transiently reduced, favoring accumulation (doubling) of 3PG, which can be rerouted to produce L-Ser (Ye et al, 2012); a bidirectional control between PP and glycolysis is active (Figure S5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation